Observation of reversible critical current performance under large compressive strain in Sr0.6K0.4Fe2As2 tapes. (25th May 2017) - Liu, F; Yao, C; Liu, H; Dai, C; Qin, J; Ci, L; Mao, Z; Zhou, C; Shi, Y; Jin, H; Wang, D; Ma, Y
Abstract: Iron-based superconductors have caused great interest regarding high-field applications due to their good properties. A common fabrication route for 122-type wires and tapes is the ex situ powder-in-tube (PIT) process. From the point of application in the high magnetic field, where high electromagnetic forces are present, the conductor strength and its tolerance to the mechanical load are important issues. In order to understand the comparatively integrated critical current characterization of the Sr-122 tape under axial strain, the so-called U-spring setup was used to test a silver-sheathed Sr0.6 K0.4 Fe2 As2 tape sample with a single core over a wide range of applied axial strain (−0.6% ∼ 0.3%). It was found that when the sample was compressed, the critical current performance showed reversiblity; meanwhile the irreversible tensile strain limit was quite low. The Sr-122/Ag tape shows very good performance under compression, and a possible conductor design should be considered to make the superconductor work at proper compressive strain states for future applications.